HIM Exclusive - HIM International - HIM Monthly : Britain's National Gay Magazine (London: Millivres)
"Fonds Suzan Daniel (FSD)Periodiciteit : maandelijksRedactie : 283 Camden High St, London NW1Vanaf (1976) 1 HIM InternationalVanaf (1978) HIM MonthlyVA Gay Times"